Survival of Very High Blood Alcohol Concentration Without Consequential Damage in a Patient Without a Previous Substance Use Disorder. Issue 4 (25th March 2016) - Malejko, Kathrin; Graf, Heiko; Gahr, Maximilian
Abstract: Intoxications with alcohol may lead to death depending on (maximum) blood alcohol concentration (BAC) and accompanying factors such as liver function, tolerance, and comedication. Death may occur due to ethanol‐induced respiratory depression and/or aspiration of gastric content (due to an impaired gag reflex); thus, securing of the airway and ventilation is occasionally necessary. A case of a 58‐year‐old female patient with depression who demonstrated a very high BAC of 8.68 gm/L (0.868%) following ingestion of large amounts of alcohol with suicidal intent is presented. Intubation and ventilation were life‐saving, and the patient did not develop any physical or consequential damage. As the patient had not regularly used alcohol or any other psychotropic agent, tolerance could be ruled out. This case emphasizes the necessity of rapid securing of the airway in patients with alcohol intoxication and respiratory depression and, furthermore, illustrates the large interindividual differences regarding ethanol susceptibility.